The Role of microRNAs in Ovarian Granulosa Cells in Health and Disease - Tu, Jiajie; Cheung, Albert Hoi-Hung; Chan, Clement Leung-Kwok; Chan, Wai-Yee (Frontiers in Endocrinology, 2019)
The granulosa cell (GC) is a critical somatic component of the ovary. It is essential for follicle development by supporting the developing oocyte, proliferating and producing sex steroids and disparate growth factors. Knowledge of the GC’s function in normal ovarian development and function, and reproductive disorders, such as polycystic ovary syndrome (PCOS) and premature ovarian failure (POF), is largely acquired through clinical studies and preclinical animal models. Recently, microRNAs have been recognized to play important regulatory roles in GC pathophysiology. Here, we examine the recent findings on the role of miRNAs in the GC, including four related signaling pathways (Transforming growth factor-β pathway, Follicle-stimulating hormones pathway, hormone-related miRNAs, Apoptosis-related pathways) and relevant diseases. Therefore miRNAs appear to be important regulators of GC function in both physiological and pathological conditions. We suggest that targeting specific microRNAs is a potential therapeutic option for treating ovary-related diseases, such as PCOS, POF and GCT.